Fabrication of biocleavable shell cross-linked hybrid micelles for controlled drug release using a reducible silica monomer. Issue 96 (22nd October 2018) - Zhang, Xianshuo; Zhang, Xiaolong; Sun, Lu; Liu, Fangjun; Wang, Mingqi; Peng, Jinlei; Wang, Yunfei; Ma, Liwei; Wang, Baoyan; Wei, Hua
Abstract : We reported the first preparation of triblock copolymer-based biocleavable shell cross-linked (SCL) hybrid micelles using a reducible silica monomer. Abstract : We report in this communication the first preparation of triblock copolymer-based biocleavable shell cross-linked (SCL) hybrid micelles using a reducible silica monomer that integrates a polymerizable methacrylate structure and in situ cross-linkers of silica precursors via a disulfide bond. The monomer developed herein offers a highly straightforward and robust strategy toward bioreducible silica-based hybrid nanoparticles for controlled drug release.